2017
DOI: 10.14260/jemds/2017/107
|View full text |Cite
|
Sign up to set email alerts
|

Role of Magnetic Resonance Imaging in Paediatric Epilepsy

Abstract: BACKGROUNDAims and Objectives 1. To identify structural abnormalities in the brain associated with Epilepsy. 2. To study the spectrum of MRI findings in patients with Epilepsy. 3. To study the aetiological factors of Epilepsy. 4. To evaluate the diagnostic efficacy of a standard MRI of the brain in children with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
1
Order By: Relevance
“…The results showed that about half of patients 47% had normal MRI while 53% had a suspicious MRI abnormality including focal cortical dysplasia (FCD), abnormal signal in the temporal lobe as well as hippocampal volume loss. Contrasted to our results, Kumari et al(Kumari, Jyothi, Chandra, Pushpanjali, & Jayalatha, 2017) showed that 41% of epileptic patients had normal MRI while 59% of them had MRI findings including space occupying lesion/tumour in left parietal and temporal lobe, open-lip schizencephaly with cortical dysplasia and sturgeweber syndrome. The current work revealed that EEG localization of the studied patients 14% were generalized, 16% left frontal, 10% left temporooccipital, 13% temporal, 27% left temporal, 10% left temporocentral onset, 10% bilateral central onset.…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed that about half of patients 47% had normal MRI while 53% had a suspicious MRI abnormality including focal cortical dysplasia (FCD), abnormal signal in the temporal lobe as well as hippocampal volume loss. Contrasted to our results, Kumari et al(Kumari, Jyothi, Chandra, Pushpanjali, & Jayalatha, 2017) showed that 41% of epileptic patients had normal MRI while 59% of them had MRI findings including space occupying lesion/tumour in left parietal and temporal lobe, open-lip schizencephaly with cortical dysplasia and sturgeweber syndrome. The current work revealed that EEG localization of the studied patients 14% were generalized, 16% left frontal, 10% left temporooccipital, 13% temporal, 27% left temporal, 10% left temporocentral onset, 10% bilateral central onset.…”
Section: Discussioncontrasting
confidence: 99%